A,I,On,The INFLUENCE OF THE CLEARANCE BETWEEN THE PUNCH AND THE MATRIX ON THE FORMATION OF BURR ON THE INSECT TEETH OF THE DEVELOPED SAW CUTTING MACHINE - Oripov, Jasurbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
The article presents the results of an analysis of the appearance of burrs on the teeth of a saw cutting machine, the value of which is in The article presents the results of an analysis of the appearance of burrs on the teeth of a saw cutting machine, the value of which is influenced by the gap between the punch (cutting knife) and the matrix, ways of removing it or reducing its geometric dimensions, it is recommended to maintain the value of the gap between the punch and the matrix and use recommendations for cold cutting technology sheet metal stamping, which corresponds to 0.03...0.06 mm for cutting saw blades. fluenced by the gap between the punch (cutting knife) and the matrix, ways of removing it or reducing its geometric dimensions, it is recommended to maintain the value of the gap between the punch and the matrix and use recommendations for cold cutting technology sheet metal stamping, which corresponds to 0.03...0.06 mm for cutting saw blades.